A good start : supporting families with a first baby : a thesis presented in partial fulfilment of the requirements for the degree of PhD in Social Policy and Social Work at Massey University, Albany, New Zealand - de Haan, Irene Anne (Massey University, 2011)
The study explored first time parents’ experiences during transition to parenthood, focussing on types and aspects of support found helpful or unhelpful. In New Zealand the state has a role in supporting new parents; yet high rates of child maltreatment indicates room for improvement in support provided. In recognising that infants have a basic right to optimal care, and in exploring how families can be better supported to provide such care, the study is aligned with a human rights approach to social work research. Twenty five women in diverse circumstances were interviewed before and after the birth of a first baby. Twelve ‘significant others’ were also interviewed, each once, after the baby’s birth. In order to build enough knowledge of participants’ experience to make pertinent recommendations for beneficial change in the system of support for families in transition to parenthood, attention was paid to gathering detail about practical realities of participants’ everyday experience. A narrative approach and a resilience perspective were used in analysing results. It was found that while keen to parent well, participants were unprepared for the realities of life with a baby. Issues they had not expected included: uncertainty associated with learning to parent; isolation; financial strain; problems linked to returning to paid employment; role and relationship change; and concern about being a ‘good’ parent. An overarching theme was ‘the constantness of it’, a phrase denoting absorption in an unremitting new routine marked by chronic tiredness and ‘24/7’ responsibility. The study indicates that first-time parents go through a process of developing competence while coping with new challenges. While financial strain was a pressing issue for participants in diverse circumstances, many wanted to ‘be a mum’ and were reluctant to use childcare and return to jobs. The data indicate that current policy and service provision does not always meet first time parents’ actual needs, including opportunities to learn infant care skills and relevant information for new fathers. A more flexible, responsive set of services might be created by customising standard services to more closely match needs and preferences of specific groups of new parents.
Keywords: First time parents; First baby; Parenting; Parenthood; Parent support